Analysis of factors influencing the budget execution of municipalities in Peru for the year 2022: a multidimensional study (Gestionar: revista de empresa y gobierno, 2023)
The study focused on identifying the determinants of budget execution in Peruvian municipalities during the period 2022. A quantitative correlational approach was used to analyze the relationship between various variables and budget execution. Statistical information collected through non-experimental cross-sectional methods was used to evaluate municipal characteristics and their correlation with budget execution. A direct relationship was observed between higher municipal classification and higher budget execution. In addition, the presence of robust computer systems, information transparency, staff training, internally generated revenues, current expenditure and the adoption of management tools were positively related to more effective budget execution. It is concluded that the importance of a solid organizational structure, diversified IT infrastructure, management transparency, staff training, sufficient internal revenues, adequate operating expenses, and the implementation of management tools to improve budget execution in Peruvian municipalities. These results provide a comprehensive framework to optimize financial practices and ensure a more efficient allocation of public resources, promoting collective development and community welfare.
Keywords: factors; budget execution; municipality; Peru